PKP-011 Amikacin accumulation in patients with normal renal function and once daily dosing based on accepted trough targets. (14th February 2016) - Juvany, R; Sanmartí, N; Leiva, E; Cobo, S; Carreres, M; Dastis, M; Dot, D; Jódar, R
Abstract : Background: In patients with normal renal function (NRF) amikacin is commonly prescribed at standard doses of 15–20 mg/kg/day assuming that there is no drug accumulation. In general, NRF is defined by glomerular filtration rate (GFR) ≥60 mL/min. Optimal amikacin trough serum levels (ATSL) should be ≤1 mg/L. Purpose: The aim of this study was to evaluate if amikacin standard dosing of 15–20 mg/kg/day is appropriate to achieve the serum level trough target for preventing drug accumulation in patients with NRF. Material and methods: Retrospective observational study of adult hospitalised patients treated with amikacin and GFR ≥60 mL/min selected from our therapeutic drug monitoring (TDM) database from January 2007 to June 2015. GFR values were estimated by the formula from the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI). Critically ill patients and haemodialysis patients were excluded. Variables collected: age, sex, GFR, weight, height, body surface area (BSA), dose regimen and ATSL. ATSL were considered supratherapeutic if >1 mg/L. Patients were also divided into two groups according to GFR values: 60–90 mL/min (A) and >90 mL/min (B). Results: 53 patiens (40 men) with 69 determinations of amikacin were selected. Median age was 71 years (28–86) and median BSA was 1.83 m 2 (1.37 to 2.28). 30 (43.5%) ATSL were classified in the GFR group A and 39 (56.5%) in the GFR group B. 30 (43%) ATSL were >1 mg/L (median 1.74 mg/L, range 1.1–10 mg/L), 21 of which were classified as group A. Amikacin dose was reduced in 26 of 30 (87%) cases, while maintained in four cases with serum levels closer to the target (between 1.1 and 1.2 mg/L). According to GFR amikacin dose was reduced in 66% of cases (20 of 30) in group A while in only 15% of cases (6 of 39) in group B. Conclusion: In adult patients with NRF, amikacin once daily dosing may cause drug accumulation on the basis of accepted trough targets, especially in patients with GFR between 60 and 90 mL/min. TDM of amikacin should be performed despite NRF to avoid drug accumulation. No conflict of interest.